Exploring Lecturers' Perceptions of First Language Influence on English Adjective Order Acquisition among EFL Learners - Prastikawati, Entika Fani; Adeoye, Moses Adeleke (Jurnal VARIDIKA, 2026)
The influence of first language (L1) on acquiring English as a Foreign Language (EFL) is a vital area of inquiry, particularly regarding specific grammatical structures such as adjective order. The purpose of this research is to systematically identify and explain how learners’ first languages affect the acquisition of English adjective order, and to provide evidence-based insights that can inform targeted instructional strategies for addressing L1-related difficulties in EFL teaching. This study adopted a quantitative research approach using a structured questionnaire designed around the research questions on EFL lecturers’ perceptions of first language (L1) influence on English adjective order, the effectiveness of teaching strategies in mitigating L1 interference, and the integration of L1 awareness into teaching and assessment practices. Statistical analyses were employed to summaries responses, identify patterns of agreement, and test differences across lecturer characteristics, ensuring objective and systematic interpretation of the data. The findings revealed distinct error patterns associated with L1 influence, indicating that learners from various language backgrounds encounter unique challenges in mastering English adjective order. Furthermore, the research introduced the concept of Adaptive Language Instruction, advocating for instructional strategies tailored to the specific linguistic profiles of learners. In conclusion, this study contributes to the field by offering a detailed understanding of the L1 influence on adjective order and practical teaching strategies that enhance EFL instruction. By integrating L1 awareness into teaching practices, educators can better support learners in navigating L1-related challenges, ultimately improving their English proficiency.